Analysis of Patients with Focal Epilepsy and Drug-Resistant Epilepsy in Italy: Evaluation of Their Characteristics, Therapeutic Pathway and the Consumption of Healthcare Resources - Perrone V; Veronesi C; Dovizio M; Ancona DD; Andretta M; Bartolini F; Cavaliere A; Chinellato A; Ciaccia A; Cillo M; De Francesco A; Enieri N; et al. (Dove Medical Press, 2022)
Valentina Perrone,1 Chiara Veronesi,1 Melania Dovizio,1 Domenica Daniela Ancona,2 Margherita Andretta,3 Fausto Bartolini,4 Arturo Cavaliere,5 Alessandro Chinellato,6 Andrea Ciaccia,7 Mariarosaria Cillo,8 Adele De Francesco,9 Nicola Enieri,6 Fulvio Ferrante,10 Simona Gentile,11 Cataldo Procacci,2 Loredana Ubertazzo,12 Adriano Vercellone,13 Domenico Lucatelli,14 Michela Procaccini,14 Luca Degli Esposti1 1CliCon S.r.l., Società Benefit-Health, Economics & Outcomes Research, Bologna, Italy; 2Dipartimento Farmaceutico, ASL BAT, Andria, Italy; 3UOC Assistenza Farmaceutica Territoriale, Azienda ULSS 8 Berica, Vicenza, Italy; 4Dipartimento Farmaceutico, USL Umbria 2, Terni, Italy; 5Farmaceutica Aziendale, ASL Viterbo, Viterbo, Italy; 6Unità Operativa Farmacia Ospedaliera, ULSS 3 Serenissima, Mestre, Italy; 7ASL Foggia, Foggia, Italy; 8Dipartimento Farmaceutico, ASL Salerno, Salerno, Italy; 9Azienda Ospedaliero-Universitaria "Mater Domini", Catanzaro, Italy; 10ASL Frosinone, Frosinone, Italy; 11Direzione Generale per la Salute, Campobasso, Italy; 12ASL Roma 4, Civitavecchia, Roma, Italy; 13ASL Napoli 3 sud, Napoli, Italy; 14Angelini Pharma, Roma, ItalyCorrespondence: Valentina Perrone, CliCon S.r.l., Società Benefit-Health, Economics & Outcomes Research, Via Murri 9, Bologna, 40137, Italy, Tel +39 3450316494, Email valentina.perrone@clicon.itPurpose: A retrospective analysis was conducted to estimate the number of patients with focal epilepsy and drug-resistant epilepsy (DRE) and their characteristics, the therapeutic patterns, the consumption of health resources in a real-world Italian setting.Patients and Methods: A retrospective study was carried out on the administrative databases of a sample of Italian Health Departments, covering approximately 8.7 million health-assisted individuals. All adult patients with at least one hospitalization for focal epilepsy and an electroencephalogram (between 01/2010 and 12/2019), and at least one prescription of antiseizure medication (ASM) (between 01/2011 and 12/2018) were included in the study. Patients with at least two treatment failures and treated with a subsequent ASM were considered DRE.Results: Overall, 1897 patients with focal epilepsy (mean age 56 years, 47% male) were identified, of which 485 (25.6%) with DRE (mean age 53 years, 43% male). Among patients with focal epilepsy and DRE, respectively, 48% and 54% had essential hypertension, 23.4% and 26.6% had cardiovascular disease, and 46.3% and 62.1% had peptic ulcer/prescription of gastric secretion inhibitors. During follow-up, patients with focal epilepsy maintained first-line treatment for 53.9 months; among these, 52% passed to the second-line, and 485 (25.6% of the total) began third-line treatment. In patients with focal epilepsy, the mean cost was € 4448 (of which € 1410 were epilepsy-related), and in DRE patients total expenditures averages € 5825 (of which € 2165 were epilepsy-related). In both patients with focal epilepsy and DRE, hospitalizations represented the most impacting item of expenditure.Conclusion: The present analysis conducted in a setting of Italian clinical practice has shown that 25% of patients with focal epilepsy were resistant to antiepileptic treatments. Furthermore, these results showed that health-care costs for the management of epileptic patients were mainly accountable for the costs related to the disease-management and to hospitalizations.Keywords: epilepsy, real-world evidence, clinical practice, pharmacoutilization, healthcare resource consumption